Crossing borders: thinkers and mathematical ideas, 1100‒1500 CE - Petrocchi, A (University of Warwick, 2021)
The present paper investigates the transmission of Indo-Arabic numerals from India to the medieval West via Arabic sources, which provides an interesting intellectual and historical background to explore knowledge transfer across cultures. The goal of this paper is to shed light on Eastern and Western cultural exchanges and, in doing so, to add new interpretative layers to understand the Mediterranean world as the melting-pot of many histories. I provide a comparative perspective by juxtaposing Western and Eastern works belonging to different textual genres and which are commonly treated separately. From these works we can glimpse how individuals involved in cross-cultural interactions understood or chose to represent their own identity and that of ideas that originated beyond their cultural and linguistic milieu. In this regard, I emphasise the role played by translators, mediators of culture, and intellectuals in perceiving foreign knowledge and how this perception was communicated through language. The literature presented in the present study illustrates active links between cultural circuits across the Mediterranean world.